The Guinness Book of More Military Blunders - Regan, Geoffrey (London Guiness Publishing Ltd., 1998)
This second collection of bizarre and baffling examples of military incompetence, from Hannibal to Saddam Hussein, includes detailed case studies which analyze the tactical errors made in battles such as Carrhae, Malplaquet, Omdurman, Passchendaele, the Kasserine Pass and Goose Green.
Include Illustrations and Index.
Keywords: Military history -- Strategy -- Military art and science